Antiplatelet Agents and Anticoagulants: From Pharmacology to Clinical Practice - Tsoumani, Maria E.; Tselepis, Alexandros D. (Current Pharmaceutical Design, 2017)
Thrombosis is the formation of potentially deadly blood clots in the artery (arterial thrombosis) or vein (venous thrombosis). Since thrombosis is one of the main causes of death worldwide, the development of antithrombotic agents is a global medical priority. They are subdivided into antiplatelet agents and anticoagulants. Antiplatelet agents inhibit clot formation by preventing platelet activation and aggregation, while anticoagulants primarily inhibit the coagulation cascade and fibrin formation. Therapeutics within each category differs with respect to the mechanism of action, time to onset, duration of effect and route of administration. In this review, we critically discuss their main pharmacodynamic and pharmacokinetic characteristics as well as recent advances in daily clinical practice.
Keywords: thrombosis